Perilaku Seks Aman pada Wanita Pekerja Seksual di Kota Padang (Berita Kedokteran Masyarakat (BKM), 2018)
Safe sex practices in female sex workers in PadangPurpose: The purpose of this study was to analyze in-depth the behavior of FSW in the HIV/ AIDS prevention in Padang.Methods: This study used a qualitative approach with in-depth interviews with 10 informants consisting of female sex workers, pimps, and related officers. The technique of determining informants using purposive sampling method.Results: The results showed that condoms were available at FSW hotspot locations, both obtained free of charge from KPA in Padang and purchased by FSW. However, not all customers want to use condoms during sexual intercourse. This proves the weak bargaining position or negotiation of FSW to customers in the use of condoms. FSW received strong support from related officers such as KPA and the health office in the HIV/ AIDS prevention, but support from FSW friend’s and pimps was still lacking.